Chill without thrill: a crossover study on whole-body cryotherapy and post-match recovery in high-level youth basketball players - Pernigoni, M.; Tessitore, A.; Digno, M.; Perazzetti, A.; Kamandulis, S.; Conte, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The intense nature of basketball match-play, combined with the increasing occurrence of congested match schedules, may lead to fatigue accumulation throughout the competitive season [1]. Therefore, the use of recovery interventions has gained popularity, with the aim of preserving players` readiness and high-level performance [2]. Among these strategies, cold water immersion has shown beneficial effects on recovery in basketball, likely due to reductions in muscle damage and inflammation [2]. However, other cold-based interventions - such as whole-body cryotherapy (WBC) - remain unexplored in basketball-specific research. Therefore, the aim of this study was to investigate the effect of post-match WBC on measures of performance, physiological and perceptual recovery following a basketball match in high-level, youth basketball players. METHODS: Using a crossover design, 17 youth male players (top-tier under-15 and under-17 Italian leagues) completed two simulated basketball matches (4x10-min quarters; 33 min of actual playing time for each player), followed by either WBC (4 min, -75 to -85°C) or placebo (CON; fictitious stimulation of the main lower limbs muscles through inactivated infrared devices). To assess the effectiveness of WBC, countermovement jump height (CMJ), change-of-direction performance, 10 and 20-m sprint times, heart rate variability (Ln-rMSSD), muscle soreness and perceived recovery (PRS) were recorded at pre-match, post-match, post-recovery and 24 h post-match. Additionally, Ln-rMSSD was recorded upon awakening on match day, and the following morning. RESULTS: Compared to CON, higher PRS values were reported in WBC at pre-match (p = 0.023, moderate effect size [ES]) and post-recovery (p = 0.026, moderate ES), while no significant between-interventions differences were found for any other variable (p > 0.05). Regarding the effect of time, our main findings revealed that 20-m sprint times (p = 0.045, small ES), Ln-rMSSD (p < 0.001, large ES) and PRS (p < 0.005, large ES) significantly deteriorated in both interventions from pre-to-post-match (i.e., acute changes), while muscle soreness worsened in WBC only (p < 0.004, large ES). Conversely, CMJ, change-of-direction performance and 10-m sprint times were unaffected by match-play in the acute phase (p > 0.05), while none of the investigated variables showed residual impairments at 24 h post-match, compared to pre-match (p > 0.05). CONCLUSION: The present findings indicate that WBC was ineffective for improving recovery of performance, cardiac autonomic activity and muscle soreness in high-level, youth male basketball players following a simulated match. Conversely, WBC might have a potentially beneficial effect on perceived recovery in the acute phase (i.e., post-recovery), although caution is advised when interpreting these findings, given the observed differences at baseline (i.e., pre-match) between WBC and the placebo intervention.